Zwischen Souveränität und Ökonomie Zugehörigkeitskonstruktionen durch die Sozialversicherung im deutsch-polnischen Verhältnis 1918-1945 - Stegner, Stefan (Studien aus dem Max-Planck-Institut für Sozialrecht und Sozialpolitik, 2018)
"International social law is often considered a technocratic matter only certain experts of welfare state administration and judicature have to deal with. This study argues to the contrary that the international coordination of social security systems expresses membership statuses to state entities. By analysing the political functionality of nationalisation and transnationalisation of social rights, it becomes evident that membership in welfare states is constructed by sovereign and economic rationalities. The latter serve as door-openers for national welfare states. Taking juridical and socio-philosophical concepts of membership of individuals in state entities as a starting point, the study analyses the legal history of ex- and inclusion of Polish workers in German social insurance from the late German Kaiserreich until the end of WWII using archival sources. It concludes by applying the findings to the debate on social human rights."